Enhancing English Writing Skills Through the Use of Digital Storytelling Media: Penelitian - Dewi Sartipa; Siti Ithriyah; Dewi Sri Kuning (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
In the era of digital transformation in education, the integration of technology in language learning has become essential, particularly in fostering writing skills among English as a Foreign Language (EFL) learners. This study aims to explore the effectiveness of digital storytelling as an instructional tool to enhance students’ English writing abilities. Using a qualitative descriptive approach through literature review, the research systematically analyzes various peer-reviewed studies, journal articles, and theoretical perspectives related to digital storytelling and writing pedagogy. The findings indicate that digital storytelling has significant pedagogical value in improving writing performance. It supports the development of organization, coherence, vocabulary usage, and narrative structure in student writing. Moreover, digital storytelling promotes self-regulated learning, creativity, critical thinking, and emotional engagement, making the writing process more meaningful and reflective. Studies reviewed also highlight increased learner motivation and autonomy, as students actively participate in planning, drafting, editing, and presenting their stories using multimedia platforms. This research also reveals the flexibility of digital storytelling across different educational levels and learning environments. It offers an inclusive and engaging approach to writing instruction, aligning with constructivist and student-centered learning models. Despite its benefits, the study identifies a gap in exploring long-term effects and its integration in routine writing practice. In conclusion, digital storytelling emerges as a powerful and practical medium to enrich English writing instruction in EFL contexts. It not only improves linguistic skills but also nurtures 21st-century competencies among learners